Copper-(Photo)Catalyzed Radical Reactions with Organic Halides - Evano, Gwilherm; Theunissen, Cédric (Synlett, 2023)
Copper is one of the most efficient and attractive metals for catalysis. In addition to their availability, low cost and limited toxicity, copper complexes are utilized to catalyze a broad variety of reactions, including examples involving radicals. For such reactions, organic halides are by far the most versatile and attractive substrates. Our contributions to the catalysis of radical reactions from organic halides with copper complexes are summarized in this account.1 Introduction2 Copper-Catalyzed Radical Cross-Coupling Reactions3 Copper-Catalyzed Radical Reactions4 Copper-Catalyzed Radical Carbonylative Cross-Coupling Reactions5 Photoinduced, Copper-Catalyzed Radical Reactions6 Conclusions and Outlook
Keywords: copper catalysis; organic halides; cross-coupling; radical reactions; copper complexes; photoredox catalysis